SEMI ACTIVE CONTROL OF FIGHTER JET LANDING GEAR COMPARING WITH PID AND FUZZY LOGIC CONTROLLER EQUIPPED MAGNETORHEOLOGICAL DAMPER - Sancak, Omer Faruk; Guclu, Rahmi (YILDIZ TECHNICAL UNIV, 2018)
This paper associated with a fighter jet landing gears that has semi active suspension system. Aircraft landing gears are most important part of the aircraft during taxi position which must be able to reduce vibrations from runway roughness. For this purpose, Magnetorheological (MR) damper is used instead of passive damper as semi active landing gear and its damping force varies by voltage controller which is applied to electromagnetic coil. In order to determine the applied voltage, fuzyy logic controller and PID controller are designed. The performance of MR damper is shown with extensive numbers of numerical simulations. The two control methods are compared with each other. It is shown that the controllers can be applicable to the system and is shown that why the semi active systems can be more preferable.
Keywords: Aircraft landing gear; seated pilot model; MR damper; taxiing analysis; semi active control; fuzzy logic control; PID control; particle swarm optimization; VIBRATION CONTROL; Engineering